PERSEPSI PELANGGAN SEPERDUA KOPI SOLO TERHADAP KUALITAS PELAYANAN - Putri, Nesia Margaretta; Hindra H, Nurnawati; Sihabuddin, Sihabuddin (Solidaritas, 2024)
Seperdua Kopi is one of the coffee shops located in Solo City, precisely at JL. Yos Sudarso No. 233, Kratonan, Serengan. Seperdua Kopi has a distinctive coffee taste resulting from a mixture of different coffee beans, such as its mainstay menu "Dailly Latte" which has a unique taste characteristic. This study was conducted to determine the perception of Seperdua Kopi Solo customers towards service quality. The theory used in this study is the perception theory according to Dedy Mulyana which states that perception is an internal process that allows us to choose, organize, and interpret stimuli from our environment and this process affects our behavior, the theory of service quality according to Tjiptono, namely service quality is a service or satisfaction service offered for sale. Service is a process consisting of a series of intangible activities that usually occur in interactions between consumers and service employees or physical resources, goods or service provider systems provided as solutions to consumer problems. This study is descriptive with qualitative methods. The results of this study conclude that Seperdua Kopi customer perceptions of service quality are positive and good. Customers are satisfied with the staff's ability to process the drink or food menu served to customers, the fast and responsive menu serving and ordering process, staff service that provides a friendly, polite and courteous attitude, staff concern in prioritizing customer needs and the comfort provided by staff through cleanliness and the atmosphere of the place. Keywords: Perception, Customer, Service Quality, Seperdua Kopi